Schenker’s First “Americanization”: George Wedge, the Institute of Musical Art, and the “Appreciation Racket” - David Carson Berry (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
A quarter of a century ago, William Rothstein first spoke of the “Americanization of Heinrich Schenker,” meaning the accommodation that had to be made to bring his ideas into the American academy. The focus of this process has largely been on activities following the Second World War. However, the earliest attempt at Americanizing Schenker seems to have come from an American-born pedagogue who had not studied with Schenker or his pupils: George A. Wedge, a theory instructor at New York’s Institute of Musical Art (a precursor to The Juilliard School). He started teaching something about Schenker in his classrooms as early as 1925, incorporated some of Schenker’s concepts into a popular harmony textbook in 1930–31, and subsequently distilled some of these ideas for the musical layperson, as part of a “middlebrow” or “appreciation” agenda that he and Olga Samaroff Stokowski advanced in books and at the Juilliard Summer School. Thus, Schenker’s route to Americanization took some previously unrecognized and “home-grown” turns along the way to the process outlined by Rothstein. In this essay, I document and contextualize Wedge’s activities in five principal sections. First, I present details about his career, and investigate how he came to encounter Schenker’s ideas. Second, I explore his writings in order to discern their Schenkerian influences (which must be filtered from related elements of American pedagogy). Third, I consider Wedge’s (and Samaroff’s) pedagogical agenda of the 1930s, which involved bringing musical education to a mass audience. Fourth, I contemplate how Wedge’s work was a portent of the “Americanized” Schenker pedagogy that developed in later years. Fifth and finally, I demonstrate how -- even beyond Wedge -- the Institute of Musical Art became a conduit for learning about Schenker, especially between 1925 and 1936/37, and I argue that its name should be added to the list of early institutions in New York at which Schenkerian ideas were communicated. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part III).